A Review Article: Mitigation Strategies for Seismic Damage in Structures - Raihana M. Ejam; Hatem Hadi Obeid (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
This in-depth review article provides a comprehensive analysis of mitigation strategies for seismic damage in structures, focusing on the importance of understanding seismic properties and implementing advanced analysis techniques. The review underscores the critical role of structural properties, including stiffness, strength, and ductility, in designing earthquake-resistant structures. By exploring a range of seismic analysis methods, such as force-based, displacement-based, and numerical approaches, the review highlights the significance of a holistic approach in assessing structural response to seismic events. Moreover, the review delves into innovative methods like subspace system identification for damage detection and statistical analysis of seismic sequences, offering promising avenues for future research. The adoption of passive energy dissipation systems and base isolation techniques emerges as key strategies in reducing seismic damage and enhancing structural resilience. Additionally, the review discusses the potential of machine learning techniques in predicting seismicity rates and improving risk management in seismic-prone areas. By combining traditional and advanced methods, this review sets the stage for further developments in seismic damage mitigation strategies. The integration of technological expertise, scientific aptitude, and interdisciplinary approaches is highlighted as essential in ensuring the built environment adapts to unforeseeable natural forces. Ultimately, this review provides a foundational resource for academics, policymakers, and practitioners in the field of earthquake mitigation and structural safety.